Where formal education meets the informal: co-creating museum palaeosciences learning programmes to enhance teaching and learning in the grade 12 South African life science classroom - Van Wyk, Grizelda (My University, 2024)
This study follows the introduction of a grade 12 human evolution workshop at the University of Witwatersrand, which was later conducted at schools as well. This study used the Cultural Historical Activity Theory as a theoretical framework with socioculturalism and community of practice as intermediate theories. This was a mixed method study and data were obtained through interviews, observations, pre-and post-tests and a common test in the district. Inductive coding was used to obtain themes. It was found that the learners as well as the teachers found the workshop very beneficial and fun. They especially referred to the hands-on nature of the workshop as the most beneficial part of the workshop. The workshop was aligned to the grade 12 curriculum, and teachers and principals found this part very beneficial. Human evolution is a topic that is found to be very controversial internationally as well as in South Africa and the acceptance of it is low. This workshop managed to increase the acceptance of human evolution amongst the grade 12 learners. The results of the pre-and post-tests indicates a significant improvement of learners’ understanding of the content after the workshop. Learners who attended the workshop, also faired significantly better in a common test than learners who did not attend the workshop. Learners’ performance improved after the workshop, whether they were from resourced or under-resourced schools. Teachers also commented on the fact that they themselves learnt a lot from the workshop, thus, indicating that it could be used for teacher development. The difference between the university-based workshop and school-based workshops were found to be that the learners enjoyed the workshop at the university more. They were able to visit the museum and link this knowledge to the workshop. The school-based workshops benefited the schools, because no teaching time was lost as the workshops were conducted in the afternoons after schooling has taken place. Principals indicated that there are many challenges to sending learners on field trips, but that they were in favour of sending their learners on field trips if these are aligned to the curriculum.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Evolution workshop; Grade 12 learners; Learning programmes; Life Science